Improving Students’ Reading Comprehension by Using Google Classroom in STKIP PGRI Bandar Lampung - Purna Wiratno; Ruri Supatmi (Departement of Mathematics Education, 2023)
Google Classroom for academic purposes supports an online learning platform. This research was conducted to investigate improving students’ reading comprehension by using Google classroom in STKIP PGRI Bandar Lampung. The questionnaire was responded by 30 undergraduate students in STKIP PGRI Bandar Lampung who learned English courses. The questionnaire was analyzed used by the researchers using SPSS.Google Classroom is suitable for learning activities, especially teaching EFL learners. Google Classroom can improve students’ reading comprehension and enrich learning activities. It can fit with the necessity of students in STKIP PGRI Bandar Lampung. It make their job easier as students.